Further opportunities for digital imaging in dental epidemiology. (July 2018) - Hogan, Richard; Goodwin, Michaela; Boothman, Nicola; Iafolla, Timothy; Pretty, Iain A.
Abstract: Dental epidemiological research permits accurate tracking of the prevalence and distribution of oral disease across population groups, enabling planning and evaluation of public health interventions and healthcare service provision. This first section of this paper aimed to review traditional assessment methods in dental epidemiology and to consider the methodological and logistical benefits provided by digital imaging, both generally and specifically in relation to an established dual-camera system. The remainder of this paper describes the results of a semi-structured examination of an image archive from previous research utilising a dual-camera system, exploring whether the diagnostic yield of the images might be increased. Common oral conditions are presented alongside suggestions of the diagnostically useful data displayed in example images. Possible scoring mechanisms are discussed with consideration of the limitations that might be encountered for each condition. The retrospective examination suggests further data is obtainable from images acquired using the dual-camera system, however, consideration should be given to how best to validate this clinically. Additionally, other imaging modalities are discussed whilst taking into account the potential limitations of the dual-camera system.